Pembuatan Sistem Pencatatan Transaksi dan Inventori Berbasis Web Pada Toko Besi Irdawanti - William Antonius; Desi Arisandi; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Toko Besi Irdawanti is a family-run business that operates in the buying and selling of scrap metal and various recyclable materials such as copper, aluminum, and cardboard. Located in Bogor City, West Java, Toko Besi Irdawanti currently uses a manual method for recording transactions and inventory, which involves handwritten paper notes. This method is prone to recording errors and inefficiencies. Therefore, digitalization is needed to improve the accuracy and efficiency of transaction and inventory records. The transaction recording system is designed to organize and store transaction data in a more orderly and systematic manner. On the other hand, the inventory management system is designed to monitor stock levels accurately and in real-time. This web-based system utilizes HTML, CSS, PHP, JavaScript, Bootstrap and a MySQL database. The system's development follows the SDLC Waterfall method and involves black-box testing, UMUX, and qualitative testing to ensure the functionality and quality of the system.